Pesticide chemistry : human welfare and the environment : proceedings of the 5th International Congress of Pesticide Chemistry, Kyoto, Japan, 29 August-4 September 1982. Volume 1, Synthesis and structure-activity relationships - Miyamoto, J.; Kearney, P. C.; Doyle, P.; Fujita, T. (IUPAC symposium series., 1983)
Pesticide Chemistry: Human Welfare and the Environment, Volume I: Synthesis and Structure-Activity Relationships covers the proceedings of the Fifth International Congress of Pesticide Chemistry. The book covers research topics that tackle both improved agricultural production and public health concerns. The papers presented in this volume are organized into three parts. The first part covers the plenary lectures that discuss the political, economic, and philosophical aspects of pesticides for human welfare and pesticide research for the improvement of human welfare. The second part discusses.